Pembentukan Karakter Anak dalam Lingkungan Pendidikan Islam Perspektif Al-Qur’an dan Hadits - Sri Atin; Nur Hidayat; Yusuf Rendi Wibowo; Kharisma Romadhon; Irfan (Jurnal Pendidikan Islam, 2024)
The basic principle of preparing a characterful and moral generation of the nation is to build the children's character based on Islamic education. It is instigated by various problematic issues about children's character that are happening and immediately need to be addressed. The purpose of this study is to reveal more about the development of children's character in the perspective of Islamic education. The research method uses the Systematic Literaure Review (SLR) type. The results of the study found that children's character problems include violence, crime, immorality, bullying and brawls. This is caused by various factors including; shallow understanding of religious knowledge, lack of supervision and guidance from family, school and community. In the perspective of Islamic education, character building includes honesty, religion, courtesy, respect, respect, compassion, care for others, and sincere friendship. Character building is the responsibility of parents, schools and communities. The three of them synergize, cooperate and communicate well in order to achieve the personality of students who have morality, ethics and civilization in line with Islamic teachings.